Case report: Suspicious laryngeal mass: a case of laryngeal lymphoma misdiagnosed as chronic inflammation - Hu, Juanjuan; Han, Baoai; Ding, Ranran; Qiu, Yue; Sun, Haiying; Zhu, Yun (Frontiers in Oncology, 2024)
This case report aims to highlight the importance of considering lymphoma as a potential differential diagnosis in patients presenting with laryngeal mass and associated cervical lymphadenopathy, particularly those with a history of chronic tonsillitis. A case of a 63-year-old male patient who underwent bilateral tonsillectomy for tumor in the left tonsil. Two months after the procedure, he developed throat discomfort, dysphagia, neck swelling and other symptoms. The patient was initially diagnosed with "tongue base mass" and chronic lymphadenitis. Partial excision of the tongue base mass was performed twice in other hospital, revealing chronic inflammation of the epithelial mucosa. Further evaluations, including electron laryngoscopy and imaging studies, were conducted to investigate the condition. A computed tomography (CT) showed irregular soft tissue density in the oropharyngeal region, along with multiple lymph nodes in the neck. Subsequent histopathological examination of the lingual base biopsy revealed peripheral T-cell lymphoma with a follicular T-helper cell phenotype. Immunohistochemical staining confirmed specific markers, while ruling out other markers. In situ hybridization testing demonstrated positivity for Epstein-Barr virus-encoded RNA, and TCRG clonality was confirmed. The duration from symptom onset to diagnosis was 2 months. This case emphasizes the importance of considering lymphoma in patients with laryngeal mass and associated cervical lymphadenopathy, especially when a history of chronic tonsillitis is present. Accurate diagnosis and early intervention are crucial for effective management and improved patient outcomes.